2015
DOI: 10.1002/ece3.1751
|View full text |Cite
|
Sign up to set email alerts
|

Priority effects of early successional insects influence late successional fungi in dead wood

Abstract: Community assembly is an integral process in all ecosystems, producing patterns of species distributions, biodiversity, and ecosystem functioning. Environmental filters and colonization history govern the assembly process, but their relative importance varies depending on the study system. Dead wood decomposition is a slow process, allowing decomposer communities to develop within a slowly changing substrate for decades. Despite this, there are few long‐term studies of priority effects from colonization histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…Invertebrates can affect fungi through preferential grazing (A' Bear et al, 2014), substrate alterations (Jacobsen et al, 2015) and…”
Section: Effect Of Invertebrate Exclusion On Fungal Community Compomentioning
confidence: 99%
See 1 more Smart Citation
“…Invertebrates can affect fungi through preferential grazing (A' Bear et al, 2014), substrate alterations (Jacobsen et al, 2015) and…”
Section: Effect Of Invertebrate Exclusion On Fungal Community Compomentioning
confidence: 99%
“…To our knowledge, this study is the first to experimentally test the effect of invertebrate exclusion on both wood decay and fungal community composition as described by DNA metabarcoding, thereby potentially linking these two responses. As invertebrates seem to influence the fungal community in a species‐specific manner (A'Bear et al, ; Jacobsen et al, ; Strid et al, ), the paucity of studies on these interactions in relation to the overwhelming number of species makes it difficult to predict the compositional change in the fungal community. As for wood decay, previous studies have shown that even in areas without termites, exclusion of invertebrates generally decreases rate of wood decay (Ulyshen & Wagner, ).…”
Section: Introductionmentioning
confidence: 99%
“…Early successional saproxylic beetles act as initiators of deadwood decomposition by creating entranceways for secondary colonizers (such as fungi). Thereby, they cause priority effects that determine the structure of subsequently colonizing fungal community and successional food chains [19]. With ongoing decay, later successional beetle species facilitate access of nitrogen-fixing bacteria and mineralizing microorganisms, so that nutrients stored in the deadwood can be recycled and reintroduced to the soil [12].…”
Section: Introductionmentioning
confidence: 99%
“…High stumps also remain standing during a long time and can be followed for decades of decay. Thus, high stumps have initiated novel studies on ecological succession which have added to the understanding of how communities assemble in deadwood (Weslien et al 2011;Jacobsen et al 2015;Jonsell et al 2019). The studies are summarized in Table 1 with respect to stump age and investigated spatial scale.…”
Section: High Stumpsmentioning
confidence: 99%
“…Stand Landscape < 2 Schroeder et al 1999;Hilszczański et al 2005;Lindhe et al 2005;Gibb et al 2006;Johansson et al 2006;Abrahamsson and Lindbladh 2006;Hjältén et al 2007;Hedgren 2007;Fossestøl andSverdrup-Thygeson 2009 Hilszczański et al 2005;Johansson et al 2006;Hjältén et al 2007;Abrahamsson 2008 3-6 Jonsell andWeslien 2003;Jonsell et al 2004Jonsell et al , 2005Lindhe et al , 2005Lindhe and Lindelöw 2004;Abrahamsson et al 2008;Westerfelt et al 2015Lindbladh et al 2007Lindbladh and Abrahamsson 2008;Westerfelt et al 2018Schroeder et al 2006Lindbladh et al 20077-10 Lindhe et al 2004Lindhe and Lindelöw 2004;Westerfelt et al 2015Westerfelt et al 2018Schroeder et al 2006Abrahamsson et al 2009;Jonsell et al 2019> 11 Weslien et al 2011Jacobsen et al 2015;Westerfelt et al 2015Westerfelt et al 2018Djupström et al 2012 high stumps was a cost-efficient way of creating habitats for red-listed insects and cryptogams (Ranius et al 2005;Jonsson et al 2006…”
Section: Treementioning
confidence: 99%